2014
DOI: 10.3233/jvr-140711
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to employment: A national survey of adults with intellectual disabilities

Abstract: BACKGROUND:The federal government has invested billions of dollars to promote employment for adults with intellectual disabilities. Despite this investment, the employment rate within this population has remained stable during the recent decades. OBJECTIVE: The objective of this study is to identify characteristics of adults with intellectual disabilities who are employed, and to understand the paths towards employment for these individuals. METHODS: Respondents included a nationally representative sample of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 20 publications
0
41
1
Order By: Relevance
“…In any case, these conclusions need for further research. This result also disagrees with the result of Siperstein et al (2014 [9]) study, which indicated that young employers attitudes towards the employment of persons with disabilities more positive compared to the elderly.…”
Section: Resultscontrasting
confidence: 90%
“…In any case, these conclusions need for further research. This result also disagrees with the result of Siperstein et al (2014 [9]) study, which indicated that young employers attitudes towards the employment of persons with disabilities more positive compared to the elderly.…”
Section: Resultscontrasting
confidence: 90%
“…Lower emotional and/or behavioural problems have been associated with the employment status of people with intellectual disabilities (Martorell, Gutierrez-Recacha, Pereda, & Ayuso-Mateos, 2008;McDermott, Martin, & Butkus, 1999;McInnes, Ozturk, McDermott, & Mann, 2010;Siperstein et al, 2014), as have absence of psychiatric symptoms (Martorell et al, 2008) The majority of the studies in this review are cross-sectional, and as such, it is not possible to attribute causality. Even in the best-quality longitudinal study identified, the authors note that they cannot confirm the direction of the relationship between change in behaviour and day occupation .…”
Section: Discussionmentioning
confidence: 99%
“…Typical forms of activity and employment opportunities for people with intellectual disabilities include segregated day programs and sheltered workshops, and supported employment (SE) in competitive settings with typical wages and ongoing individualized support services (Owen et al, 2015). In view of the impact of employment on health and well-being, internationally policy concerning people with intellectual disabilities has been directed towards improving the employment opportunities of people with intellectual disabilities (Blamires, 2015;Siperstein, Heyman, & Stokes, 2014), with policy favouring community-based employment (Beyer, Brown, Akandi, & Rapley, 2010). It has been estimated that 65% of people with intellectual disabilities in England without a job would like one (Emerson, Malam, Davies, & Spencer, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In S1, we measured employment barriers that are well documented in the literature as constraining employment opportunities (Macali, 2006;Siperstein, Heyman, & Stokes, 2014;Tuckerman et al ., 2012) . Clients reported whether they experienced employment disadvantage as a function of intellectual, physical, and/or mental disabilities .…”
Section: Methodsmentioning
confidence: 99%